EFFECT OF LYKAMIN ON GROWTH AND BIOCHEMICAL COMPOSITION OF LONG WHISKERED CATFISH, MYSTUS GULlO (HAMILTON) FINGERLINGS UNDER LABORATORY CONDITIONS - Rajkumar, M.; Kumaraguruvasagam, K. P.; Maheskumar, K.; Shanmugam, A. (Journal of Indian Fisheries Association, 2015)
A growth trial was conducted to test the effect of Lykamin (dietarysupplement) on growth, survival and feed conversion in Mystus gulio. Fourisoproteic diets were formulated by incorporating the growth promoter,Lykamin at the levels of 0, 0.25, 0.50 and 0. 75% diet. The crude proteincontent was 30% in each diet. The diets were fed to triplicate groups ofcatfish fingerlings twice daily at a level of 5% of the total body weight for120 days. Regular fortnightly sampling was done to evaluate the growthperformance of the experimental animals. Water quality parameters duringthe experimental period were maintained within the range suitable for catfish.The results showed better specific growth rate, weight gain, protein efficiencyratio and feed conversion ratio in the group which was given 0.75% Lykamindiet.Key words: Lykamin, Mystus gulio, growth, survival, proximatecomposition